Maximasi Kuat Tekan Beton - Lukito Prasetyo (Department Industrial Engineering, University of Muhammadiyah Malang, 2010)
Concrete mixing obtained from the fine aggregate and coarse aggregate is sand, stonebroken by adding sufficient adhesive cement and water as supporting material for purposesof chemical reactions during the process of concrete hardening and treatment progress, andmay also be additional material that could serve to strengthen or accelerate the development ofconcrete strength. Therefore, in order to obtain concrete with a light weight, one of which is toreplace the coarse aggregate is commonly used with natural stone aggregate is an alternativethat has a lighter weight but has the major attributes that do not differ greatly. The methodused in this study by testing it against a strong press, elastic modulus, split tensile strength,density, porosity. Increased modulus of elasticity of the variation in aggregate gradation gradationsI to III of variation 14.03%. On a good variety of aggregate inter-aggregate contact areawill be smaller so that the number of pores (porosity) of concrete produced would be smaller.With a small contact area porosity and the amount of cement needed in a similar treatment willbe less. The more small porosity variations in the use of aggregate gradation will memyebabkanconcrete gravity value greater. Small porosity values which will make the concrete moredense so that the stronger the resulting press will be great. In the strong increase in press andconcrete, will be followed by a rise in value of split tensile strength and modulus of elasticityof concrete.